99mTc-Selenium-NPs as SPECT Tracers: Radio Synthesis and Biological Evaluation - Akhilesh Kumar Singh; Mohd. Faheem; Amit Jaiswal; Malleswari Ponnala; Sanjay Gambhir; Manish Dixit (Chemistry Proceedings)
As the usage of nano-sized complexes in biomedical applications has grown significantly over the past ten years, nanoparticles are now playing a significant role in the enhancement and revolution of medical applications. It may be due primarily to the novel and exceptional electrical, optical, photo-responsive, and catalytic capabilities displayed by particles with sizes ranging from 1 to 100 nm. The radiolabelled nanoparticles refer to the process of incorporating radioactive isotopes into nanoparticles. This technique enables the nanoparticles to be tracked, imaged and monitored using various imaging techniques, such as Single-Photon Emission Computed Tomography (SPECT/CT) or Positron Emission Tomography (PET). They play a crucial role in understanding the biodistribution, pharmacokinetics, and targeted delivery of nanoparticles to biological systems. In this study, selenium-based nanoparticles (Se-NPs) were explored for imaging potential as these are usable due to their size, surface, and kinetics, as well as their ability to be functionalised. The 99mTechnicium (99mTc) radionuclide was used to radiolabel the bio-inspired highly dispersed over grown endophytic fungus Fusarium oxysporum selenium NP using conventional radiochemistry protocol. The radiolabelling yield was found to be 94.5 ± 3% and analysed by various analytical tools. The synthesized 99mTc-Se-NPs were assessed through In-vitro stability, and their In-vivo biodistribution was performed. The accumulation of post six-hour data was primarily seen in the liver (around 3.4% ID/g) and lungs (about 2.2% ID/g). These Se-NPs can be used as an imaging agent for lung and liver disorders because these NPs quickly pass through the kidneys are expelled via urine and show a long retention time in the body. These properties of 99mTc-Se-NPs can be used for non-invasive imaging via SPECT.